9 - 2(x + 6) =
9 - 2x - 12 =
-2x - 3 <=
Answer:
a
x
2
+
b
x
+
c
=
0
the two roots of the equation take the form
x
1
,
2
=
−
b
±
√
b
2
−
4
a
c
2
a
So, start by adding
−
5
to both sides of the equation to get
2
x
2
+
x
−
5
=
5
−
5
2
x
2
+
x
−
5
=
0
Notice that you have
a
=
2
,
b
=
1
, and
c
=
−
5
. This means that the two solutions will be
x
1
,
2
=
−
1
±
√
1
2
−
4
⋅
2
⋅
(
−
5
)
2
⋅
2
x
1
,
2
=
−
1
±
√
41
4
You can simplify this if you want to get
x
1
=
−
1
+
√
41
4
≅
1.35078
and
x
2
=
−
1
−
√
41
4
≅
−
1.85078
Answer:
Solution given
Sin Q=opposite/hypotenuse=28/29
<u>28/29</u><u> </u><u>is</u><u>. </u><u>a</u><u> </u><u>required</u><u> </u><u>answer</u><u>.</u><u />
You can just do the inverse operation. 39 divied by 10 = 3.9
so 3.9 *10 =39
hope it helped
The surface area of a cylinder is the sum of the area of the two ends and the lateral area.
.. surface area = 2*(end area) +(lateral area)
.. = 2*(π*r^2) +(2π*r*h)
.. = 2π*r*(r +h)
.. = 2*3.14*(8 in)*(8 in +8 in)
.. = 3.14*256 in^2
.. ≈ 803.8 in^2
The 3rd selection is appropriate.